I Stalk Myself More than I Should: Online Narratives to Disrupt and Investigate Interveillance and Digital Bodies Politics within Centralised Social Media Platforms (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
Today we find ourselves immersed in digital environments made available by centralised social media platforms on a daily basis. While these platforms did provide users expanded connectivity and visibility, they also confined the same user in an economic system focused on collection and commodification of personal data for profit, and in return used them as resources of free labour. In light of this analysis, is it possible to carry out an artistic practice within centralised social media platforms, therefore take an active part in them, while remaining critically engaged, in the attempt to highlight some of the structural dynamics and problems of these realities?In this paper some fundamental aspects of the aforementioned channels will be discussed through the analysis of selected works and two methods utilised by the author to avoid the culture of interveillance.
Keywords: Centralised social media platforms; Interveillance; Online narratives; Digital bodies; Subversion